The European civil law codification and the challenges of private law in Latin America - Gonzáles, Carlos Antonio Agurto (2019)
In the last decade of the 20th century, the idea of a European common law has re-emerged, linked to a broader process of political unification and that focus the construction of a European identity. The rules and directives framing the field of public law transcend the level of civil law stimulating the debate about the centrality of the person and social justice respect present in civil codes in European and South American continent.